Field notes contributed by Peter C. Petersen, January 26, 1982 - Petersen, Peter C.et al (1982)
Field notes were contributed by Peter C. Petersen and other observers. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of winter 1981-1982. Epson - sheet feed